Speaking Out: Introductory - Ikey, Olivia (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2020)
ContextConference retranscription « Living in Northern Quebec: Issues and Challenges of Appropriate and Meaningful Living Environments for Inuit Communities”, Special session “LINQ’s Day-Long Special Session”, Inuit Studies Conference 2019. October 3, 2019, Université du Québec à Montréal.